Dike Inflation Process Beneath Sakurajima Volcano, Japan, During the Earthquake Swarm of August 15, 2015 - Koike, Midori; Nakamichi, Haruhisa (Frontiers in Earth Science, 2021)
A swarm of volcano-tectonic (VT) earthquakes associated with rapid ground deformation occurred beneath Sakurajima volcano, Japan, on August 15, 2015. We determined the hypocenters of the VT earthquake swarm using the arrival times and cross-correlation data from earthquake waveforms based on the double-difference method. We estimated the focal mechanisms of the VT swarm using the P-wave polarities and amplitude ratio of the P- and S-waves and then classified the focal mechanisms and pressure (P)- and tension (T)-axes of the azimuths. The results indicate spatiotemporal changes of the distributions of the hypocenters and P- and T-axes. The hypocenters are distributed at depths of 0.3–1 km in the 7:00–10:30 JST period, and are located at depths of 0.3–3 km in the 10:30–12:00 period during which the seismic activity and change rate of the ground deformation are the largest. At 12:00–24:00, the hypocenters are distributed in shallow and deep clusters at depths of 0.2–1 and 1.5–3.5 km, respectively. Based on the ground deformation, the dike is located between the two clusters. The strike and opening directions of the dike are parallel to the NE–SW and NW–SE directions, respectively, corresponding to the regional maximum compression and extension stress around Sakurajima. Normal and strike-slip faulting focal mechanisms are dominant. The T-axes of the shallow cluster are distributed parallel to the opening direction of the dike. The P-axes of the deep cluster exhibit a pattern corresponding to the NE–SW direction and the T-axes are distributed in the NW–SE direction. In contrast, a 90° rotated pattern of strike-slip faulting is also observed at the deeper cluster at 12:00–24:00, where the P-axes are distributed in the NW–SE direction and the T-axes are distributed in the NE–SW direction. This reflects the change in the stress field due to the dike inflation during the earthquake generation, and indicates that the alteration of stress in the vicinity of the dike due to the dike inflation and VT earthquakes are induced by the differential stress exceeding the fracture strength of the rock. The VT earthquake swarm is initiated at shallow depth and then extended to greater depth as the dike inflation progresses.